1990
DOI: 10.1007/bf02470711
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience of biliary tract carcinoma associated with anomalous union of the pancreaticobiliary ductal system

Abstract: Between 1978 and 1988, 15 patients with gallbladder cancer and 2 patients with bile duct cancer were seen among 49 patients with anomalous union of the pancreaticobiliary ductal system. Radiographic findings revealed two types of this anomalous condition: one in which the pancreatic duct entered the common bile duct (type 1) and one in which the common bile duct entered the pancreatic duct (type 2). In gallbladder cancer, the common bile duct presented no dilatation, or in some patients, mild dilatation, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The amylase levels in bile were elevated in 6 patients with HCPBD, and those of 3 cases were 110,000 IU/l, as typically seen in PBM [12]. The presence of reflux of pancreatic juice into the bile duct may account for the relatively high frequency of gallbladder carcinomas associated with HCPBD, as has been suggested in cases of PBM.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The amylase levels in bile were elevated in 6 patients with HCPBD, and those of 3 cases were 110,000 IU/l, as typically seen in PBM [12]. The presence of reflux of pancreatic juice into the bile duct may account for the relatively high frequency of gallbladder carcinomas associated with HCPBD, as has been suggested in cases of PBM.…”
Section: Discussionmentioning
confidence: 67%
“…First of all, 12% of the HCPBD cases had a gallbladder carcinoma, although the incidence was less than in those with PBM without biliary dilatation. In cases of gallbladder carcinomas associated with PBM, the frequency of concomitant cholelithiasis is characteristically low, and the age of these patients at the time of diagnosis is typically 10 years younger than in the patients without PBM [12,13]. The average age of the patients with gallbladder carcinomas associated with HCPBD is between that of patients with PBM without biliary dilatation and that of patients without the maljunctions.…”
Section: Discussionmentioning
confidence: 94%
“…The etiology of biliary cancer and the pathologic changes following AJPBD are not clear, although many researchers have investigated this issue. [1][2][3][4] It was recently reported that cytokines were related to the pathogenesis of some biliary diseases. [5][6][7][8][9] We have previously shown that interleukin 6 (IL-6) and tumor necrosis factor α (TNF α) may play an important role in retarding the resolution of obstructive jaundice after percutaneous transhepatic cholangio-drainage (PTCD), 5,6 that bile IL-6 levels are elevated after biliary drainage for intrahepatic gallstones, and that bile IL-6 may participate in pathologic changes such as chronic proliferative cholangitis or hepatic atrophy associated with intrahepatic gallstones.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with PBM, gallstones do not appear to contribute to carcinogenesis, based on the low rate of gallstone detection [45]. The patients with gallbladder cancer associated with PBM without biliary dilation were significantly younger than those without PBM [43, 45]. The mechanism of carcinogenesis in PBM is considered to be related to the presence of pancreatic juice refluxed into the biliary tract.…”
Section: Clinical Implications Of Biliopancreatic and Pancreatobiliarmentioning
confidence: 99%
“…The etiology of gallbladder cancer in patients with PBM has not been fully clarified. In patients with PBM, gallstones do not appear to contribute to carcinogenesis, based on the low rate of gallstone detection [45]. The patients with gallbladder cancer associated with PBM without biliary dilation were significantly younger than those without PBM [43, 45].…”
Section: Clinical Implications Of Biliopancreatic and Pancreatobiliarmentioning
confidence: 99%